2017
DOI: 10.13005/ojc/330641
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Milling on Physicochemical Properties of Usnic Acid Isolated from Usnea sp.

Abstract: SUsnic acid is the secondary metabolite found in lichens, particularly Usnea sp which has considerable pharmacological activities. However, the used of usnic acid is still limited due to poorly soluble in water. The aim of this study was to investigate the impact of milling process to physicochemical properties of usnic acid. Usnic acid was isolated from Usnea sp by soxhlet extraction method. The crystal of usnic acid was then milled in three different times: 30, 60 and 90 minutes. The characterization of inta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 17 publications
1
15
0
1
Order By: Relevance
“…It is known that usnic acid is soluble in the both solvents, acetone and DMSO [30]; in acetone, the solubility of usnic acid is two times higher than in DMSO: 0.77 g/100 mL in acetone [31] and in DMSO it is 0.4 g/100 mL, warmed [32]. These data explain the approximately double content of usnic acid in UBE dissolved in acetone compared to that solubilized in DMSO.…”
Section: Discussionmentioning
confidence: 94%
“…It is known that usnic acid is soluble in the both solvents, acetone and DMSO [30]; in acetone, the solubility of usnic acid is two times higher than in DMSO: 0.77 g/100 mL in acetone [31] and in DMSO it is 0.4 g/100 mL, warmed [32]. These data explain the approximately double content of usnic acid in UBE dissolved in acetone compared to that solubilized in DMSO.…”
Section: Discussionmentioning
confidence: 94%
“…was collected from Mt. Merapi (West Sumatera, Indonesia) and the isolation procedure of usnic acid from Usnea sp was explained in previous work 16 . HPMC 2910 (Shin-Etsu Chemical, Japan), chloroform (Merck, Germany), ethanol (Bratachem, Indonesia), and distilled water.…”
Section: Methodsmentioning
confidence: 99%
“…Solid dispersion of usnic acid PVP K-30 was prepared as described in previous work [15]. Usnic acid and PVP K-30 at ratio 1:2 (w/w) were dispersed in 100 mL distilled water and stirred until homogenous.…”
Section: Preparation Solid Dispersionmentioning
confidence: 99%
“…This finite number of product is likely due to low solubility of usnic acid in water (0.01 g/100 mL) [8]. Some efforts have been done to increase the solubility of usnic acid, such as complex formation using cyclodextrin [13], microencapsulation using polymer PLGA [14], milling process [15] and preparation in solid dispersion using HPMC [16]. Our recent study has shown enhancement of usnic acid by preparing it in solid dispersion using poly-vinyl-pirolidon (PVP) K-30 and its potency as an anti-oxidant was in accordance with the solubility result [17].…”
Section: Introductionmentioning
confidence: 99%